Typological features of syntactic structures of the German language and the importance of grammar exercises in their acquisition - Raxmanov , Botir (The Lingua Spectrum, 2025)
The article examines the syntactic constructions of the German language, including simple sentences, and their comparative analysis with the Uzbek language. The features and characteristics of this type of speech are highlighted. The article examines the similarities and differences between German and Uzbek sentences, as well as how important these aspects are in learning the language. Both languages are originally from different language families, and the genetic diversity between them is clearly visible and causes a number of difficulties in the process of learning German. In particular, one can note the strict word order and grammatical patterns of German sentences. To solve these problems, this article describes several strategies that can be used with grammar exercises. The amount of grammar materials selected for practical exercises should be sufficient to ensure the level of communication envisaged by the language programs, and the possibility of their acquisition should also be based on real conditions. It is explained that these exercises are divided into several types based on their functional aspect.